2016
DOI: 10.1007/s10689-015-9864-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of immunohistochemistry, copy number aberrations and epigenetic disorders with BRCAness pattern in hereditary and sporadic breast cancer

Abstract: The study aims to identify the relevance of immunohistochemistry (IHC), copy number aberrations (CNA) and epigenetic disorders in BRCAness breast cancers (BCs). We studied 95 paraffin included BCs, of which 41 carried BRCA1/BRCA2 germline mutations and 54 were non hereditary (BRCAX/Sporadic). Samples were assessed for BRCA1ness and CNAs by Multiplex Ligation-dependent Probe Amplification (MLPA); promoter methylation (PM) was assessed by methylation-specific-MLPA and the expression of miR-4417, miR-423-3p, miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…Recently, cellular miR‐590‐5p has been shown to play important roles in tumorigenesis and metastasis of various cancers where it was shown to function as either a tumor suppressor or an oncomiR based on its target(s) in the respective cancers. Its expression was found to be downregulated in breast, hepatocellular, colorectal, and lung cancer tissues, and targeted the Wnt/β‐catenin pathway, SOX2 (SRY‐box 2), TGF‐βRII (transforming growth factor beta receptor 2), NF90/VEGFA (nuclear factor 90/vascular endothelial growth factor A) and GAB1 (GRB2 associated binding protein A) which promote cancer growth and progression . Likewise, miR‐590‐5p oncogenic properties were reported in gastric, cervical, vulvar, and clear cell renal cancer, where it targets RECK (reversion inducing cysteine rich protein with kazal motifs), CHL1 (close homolog of L1), TGF‐βRII, and PBRM1 (Polybromo 1), respectively, and regulates cell proliferation, migration and invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, different expression patterns of miR-423 have been reported in various types of cancers, such as under-expression in mesothelioma, [14] oral cancer, [40] inconsistent result for colorectal cancer, [4143] while there was over-expression in head and neck cancer, [15] laryngeal carcinoma, [44] female genital system neoplasms (breast, cervical and endometrial), [16, 4547] and most of the digestive system neoplasms (gastric, pancreatic, hepatocellular) [4850, 51]. Some studies indicated that miR-423 acts as tumor suppressor in oral cancer, [40] as oncogene in hepatocellular carcinoma, [44, 51] but inconsistent results in breast cancer [52, 53]. Additionally, only two studies suggested that the C to A substitution in rs6505162 promotes the production of mature miR-423 in cell lines from breast cancer and endometrial carcinoma, [53, 54] but the SNP was not correlated with expression of miR-423 in esophageal squamous cell carcinoma [26].…”
Section: Discussionmentioning
confidence: 99%